Observation and theory of whistler wave generation by high‐power HF waves. Issue 3 (31st March 2013) - Kuo, Spencer; Cheng, Wei‐Te; Pradipta, R.; Lee, M. C.; Snyder, Arnold
Abstract [1] Summer midnight and afternoon VLF wave generation comparison experiments were conducted on 25 July and 27 July 2011, respectively, using two CW HF X‐mode waves with 11 VLF frequency differences from 2 to 21.5 kHz. The background magnetic variations were at comparable levels. During the afternoon experiment, the D region absorption was significant and increasing. The number of the ionogram echoes decreased during the afternoon experiment. VLF signals were detected from 2 to 7.6 kHz in both experiments, showing an inverse frequency dependence of intensity, although signal intensity (except at 5.5 kHz) detected during the midnight experiment was stronger than the corresponding afternoon intensity before observing a decrease of the number of ionogram echoes. However, VLF signals from 11.5 to 21.5 (except at 19.6 kHz) were also generated in the afternoon experiment concurrent with a decrease of the O‐mode ionosonde echoes from 2 to 4 MHz. The concurrence of a decrease of the afternoon ionogram echoes, the unexpected generation of VLF waves at higher frequencies, and the increasing D region absorption throughout the experiment may be explained by the generation of large‐scale density irregularities, which scatter the ionosonde signals as well as couple with the modulated electrojet to generate whistler waves. A theoretical formulation of the coupling mechanism for the whistler wave generation is presented.